Can Trustworthiness in a Supply Chain Be Signaled? - Beer, Ruth; Ahn, Hyun-Soo; Leider, Stephen (Management Science, 2018)
The relationship between a buyer and its suppliers often relies on factors beyond the terms of a contractual agreement. Buyers can therefore benefit from identifying trustworthy suppliers. We argue that precontractual actions by a supplier, for example making costly buyer-specific investments without a long-term contract, can signal a supplier’s trustworthiness. We develop a theoretical model to reflect supplier trustworthiness, and determine when a buyer can benefit from identifying trustworthy suppliers. We show that costly relationship-specific investments can serve as a signal of trustworthiness, and that supply chain profits increase when trustworthy suppliers are able to identify themselves in this fashion. We demonstrate the importance of the signaling mechanism using laboratory experiments. The experimental results show that relationship-specific investments lead to more collaborative transactions, with buyers offering higher prices and suppliers returning higher-quality products. This results in increased profits for both buyers and suppliers. Additionally, we design a treatment which shuts down the signaling mechanism and show that the benefits of the buyer-specific investment are no longer present in this case. Finally, we show that the benefits of buyer-specific investments for both suppliers and buyers are strengthened when firms interact repeatedly. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2817 . This paper was accepted by Yossi Aviv, operations management.